Relating transformation process, eco-design, composition and sensory quality in cheeses using PO2 ontology. (May 2019) - Pénicaud, Caroline; Ibanescu, Liliana; Allard, Thomas; Fonseca, Fernanda; Dervaux, Stéphane; Perret, Bruno; Guillemin, Hervé; Buchin, Solange; Salles, Christian; Dibie, Juliette; Guichard, Elisabeth
Abstract: To provide answers to sustainability challenges, a database called BaGaTel, guided by the PO 2 ontology, has been built to integrate data to reformulate dairy products taking into account nutritional and sensory properties together with environmental concerns. In this paper, BaGaTel was queried to address questions dealing with the eco-design of hard cheese processing, in relation to composition, sensory quality and rheological properties. For the formulation of hard cheese, BaGaTel made it possible to estimate missing data in a dataset supposing that samples have common characteristics. For environmental concerns, BaGaTel gave hints about relevant data that need to be acquired and made possible the estimation of missing data. The common vocabulary and structure provided by the PO 2 ontology allowed combining and integrating into BaGaTel data from different projects, giving relevant answers to different questions, and therefore proving its suitability as a support tool for multi-criteria assessment of food systems.